Biomechanical considerations in goal-kicking accuracy: Application of an inertial measurement system - Blair, S. J. (Victoria University., 2019)
Goal-kicking is an important skill in Australian Football (AF), accounting for approximately 62% of points scored during a match (Anderson et al., 2018). Despite its importance, little biomechanical research has examined the key technical characteristics underpinning the skill. The aims of this thesis were to validate a methodological approach to enable quantification of goal-kicking kinematics in a field environment, and examine goal-kicking technique and identify technical factors associated with accuracy. In Chapters 3 and 4, the Xsens inertial measurement system (IMS) was validated against a Vicon motion capture system (MAS) when measuring lower extremity and pelvis kinematics. Trivial to small mean differences (0.2-10.1%) and measurement error (0.1-7.9%) were found between the IMS and MAS across all parameters, advocating the use of IMS to quantify kicking kinematics. In Chapter 5, the effect of modifying the task constraints on accurate goal-kicking was explored. Increasing the distance of the shot from goals (30 m to 40 m) required substantially greater joint range of motion (knee and hip), with higher linear (foot speed) and angular (knee and shank) velocities. Altering the angle of the shot (0 to 45°) had no substantial influence on accurate goal-kicking technique. Findings indicated adjustments in goal-kicking technique may be required dependent on the location of the shot. In Chapter 6, 18 elite to sub-elite AF players performed 15 x 30 m goal-kicks in-front of goals and technique was examined on group-basis. A number of substantial kinematic differences were identified between accurate and inaccurate goal-kicks. For example, accurate goal-kicks were characterised by substantially less kick-leg joint range of motion (ankle, knee and hip), lower linear (com, foot speed) and angular (knee and shank) velocities, with less support-leg knee flexion during the kicking phase. In addition, a number of substantial linear and quadratic relationships were reported between technical parameters and accuracy. Findings indicated that many factors influence goal-kicking accuracy in AF; ranging from technical errors in the player`s approach, configuration of their support-leg and kick-leg motions, through to follow-through position. In Chapter 7, goal-kicking data from chapter 6 was examined on individual-basis. All players demonstrated substantial kinematic differences between accurate and inaccurate goal-kicks, along with substantial relationships between kinematic parameters and accuracy, but these were individual-specific. A combination of both a group and individual-based analysis provided a more thorough understanding of technical factors which influence goal-kicking technique in AF. The body of work in this thesis provides: 1) validation of a methodological approach to quantify kicking biomechanics, and 2) a comprehensive understanding of technical factors associated with goal-kicking accuracy in AF, and 3) recommendations for both research and coaching practice.